2019
DOI: 10.15282/jmes.13.3.2019.12.0438
|View full text |Cite
|
Sign up to set email alerts
|

Failure study of the woven composite material: 2.5 D carbon fabric/ resin epoxy

Abstract: In this paper an experimental analysis of the failure of a single layer woven fabric composite 2.5 D  G1151/ Resin Epoxy through a tensile tests at 0°, 45° and 90° is investigated. In addition a FE simulation of failure were elaborated through multiscale modeling method, micro then meso then macro scale. The microscale simulation was elaborated on ABAQUS standard simulation of a 3D unit cell of random fibers distribution of a single yarn. The meso scale simulation developed on MATLAB. The meso approach based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…where t , j , and w are the lengths of the thinner CNT, the junction region, and the wider CNTs, respectively. As aforementioned, the chirality of the connected CNTs for linearly-joined CNT was (5,5) and (10,10) armchair tube. For the case of angle-adjoined hybrids, a (5,5) armchair CNT is joined with a (10,0) zigzag CNT.…”
Section: Modelling Detailsmentioning
confidence: 88%
See 1 more Smart Citation
“…where t , j , and w are the lengths of the thinner CNT, the junction region, and the wider CNTs, respectively. As aforementioned, the chirality of the connected CNTs for linearly-joined CNT was (5,5) and (10,10) armchair tube. For the case of angle-adjoined hybrids, a (5,5) armchair CNT is joined with a (10,0) zigzag CNT.…”
Section: Modelling Detailsmentioning
confidence: 88%
“…Carbon Nanotubes (CNTs) and their degenerated modifications including nanocones, capped CNTs, fullerene, Yjunctions, linearly-joined and angle-adjoined CNTs, are a class of promising low-dimensional materials used in the electronics, composites, and energy conversion areas, which performance are directly related to their mechanical properties and stabilities [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The buckling of nanomaterials under compression loading, is influenced by the physical height of the models, their axial symmetry, relative position to normal reference plane and their fixation mode.…”
Section: Introductionmentioning
confidence: 99%
“…Patch repairing method is one of the most economical techniques which are used to repair damaged structures. Healing cracked structure using composite patch has increased considerably in recent years [5][6][7]. Patch is bonded at damaged area to support a structure against different types of external loading.…”
Section: Introductionmentioning
confidence: 99%
“…− and x + in Equations (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). indicate the location immediately before and after connection points.…”
mentioning
confidence: 99%
“…It was found that FE simulation shows a good agreement with experimental result on the tensile properties. From author point of view, this study significantly contributes in cost and time saving because the failure mode of the investigated material can be predicted using a multiscale simulation approach and potentially being applied to other composite materials [17].…”
Section: Introductionmentioning
confidence: 99%